Prosedur Naturaliasi Atlet Sepak Bola Asing Ditinjau dari Undang-Undang Kewarganegaraan - Rokilah Rokilah; Dwi Nurina Pitasari; Fitria Agustin (JURNAL HAK : Kajian Ilmu Hukum, Administrasi Negara, dan Komunikasi, 2026)
In every territory of the country there are residents. Not all residents of a country are citizens, but they can be foreigners. Residents of a country can be divided into two, namely citizens and foreigners. Citizens are one of the essential elements and the main elements of a country who have rights and obligations that need to be protected and their implementation guaranteed. One way to obtain Indonesian citizenship is citizenship (naturalization). Foreigners who render service to the state or because of the interests of the state, their citizenship can be done through special naturalization. The purpose of this study was to determine the procedure for naturalization of soccer athletes and to determine the rights and obligations of naturalized athletes to the state. This type of research is a normative juridical research, using a research approach, namely the statutory approach. The data collection method used is library research. The results of the study indicate that the procedure for applying for naturalization of foreign soccer athletes does not have many requirements, this is due to the interests of the state so that the naturalization application process is carried out easily and quickly, while the rights and obligations of naturalized players to the state are the same as Indonesian citizens in general but cannot become a Candidate for President and Vice President due to not meeting the requirements for birth in Indonesia.